Molecular insights into proliferation and inflammation in actinic keratosis and photodynamic therapy: a comprehensive review of proliferation and inflammation markers - Ceryn, Justyna; Lesiak, Aleksandra; Ciążyńska, Magdalena; Narbutt, Joanna (Contemporary Oncology/Współczesna Onkologia, 2025)
Actinic keratosis (AK) is a common precancerous skin lesion with the potential to progress into cutaneous squamous cell carcinoma (cSCC). Understanding molecular markers involved in AK pathogenesis can aid in assessing disease severity, monitoring treatment response, and identifying patients at risk of malignant transformation. This review examines key biomarkers, including Ki-67, p53, matrix metalloproteinases (MMPs), cyclooxygenase-2 (COX-2), and minichromosome maintenance protein 2 (MCM2), focusing on their role in AK progression and response to photodynamic therapy. Ki-67, a proliferation marker, declines following successful AK treatment, making it a useful therapeutic indicator. p53 mutations, common in AK, are linked to disease progression, but post-treatment persistence of mutant cells suggests the need for multiple therapy sessions. MMP-1 and MMP-2 contribute to extracellular matrix remodeling and may serve as markers of treatment efficacy. COX-2, associated with inflammation, is upregulated in AK, but its prognostic significance remains uncertain. MCM2 expression correlates with AK severity and proliferation, yet its role in cSCC progression requires further investigation. These findings highlight the importance of molecular biomarkers in AK diagnosis and treatment monitoring, suggesting that while Ki-67 and MMPs may be valuable therapeutic markers, additional research is needed to fully integrate these biomarkers into clinical practice.